Melatonin Enhances Antioxidant Defense Systems and Stress Tolerance in Plants under Variable Environmental Conditions - Ihsan Muhammad; Shah Fahad; Ahlam Khalofah; Bingsong Zheng; Weijun Shen (Rice)
Abstract Melatonin (Mel), a multifunctional molecule, has emerged as a pivotal regulator of plant stress responses, enhancing antioxidant defenses, and modulating metabolic pathways. This meta-analysis evaluated the role of Mel in mitigating various abiotic stresses, including salinity, drought, heavy metals, light intensity, and humidity, across diverse experimental conditions in rice crop. The findings reveal significant improvements in enzymatic antioxidant activities such as superoxide dismutase (SOD), catalase (CAT), peroxidase (POD), and ascorbate peroxidase (APX), with notable increases in POD (77%) and CAT (61%) activities under hydroponic application. Mel application reduced oxidative stress markers, such as hydrogen peroxide (H2O2) and malondialdehyde (MDA), by up to 45% and 54%, respectively, highlighting its capacity to alleviate cellular damage under stress conditions. Additionally, Mel enhanced osmotic regulator such as proline, soluble sugar, and protein accumulation, contributing to osmotic adjustment, with an exceptional increase of 987% proline contents in Thailand. Experimental type and application methods significantly influenced the efficacy of Mel. Hydroponic treatments and seed soaking methods consistently showed the highest improvement in stress tolerance, while field experiments exhibited variability. The effects were also modulated by light intensity and humidity. Under light intensity of 150 µmol m⁻2 s⁻1, Mel enhanced antioxidant activities and reduced oxidative damage, while humidity at 70–75% showed the highest stress alleviation effects. These findings highlight Mel's complex contribution to increasing plant resilience by control of antioxidant enzymes, reduction of oxidative damage, and enhancement of osmotic adaptations under abiotic pressures. The present study offers a thorough knowledge of Mel's potential as a plant growth regulator, therefore guiding sustainable development under demanding environmental conditions.